Data Transparency of Legislative Candidates Viewed from the Theory of Popular Sovereignty - Manao, Martin Luther (PT FORMOSA CENDEKIA GLOBAL, 2024)
A democratic country has a special characteristic, namely the direct election of leaders and representatives of the people. The direct implementation of general elections in Indonesia has problems, namely the lack of openness of election participants to publish their profiles or data. In any election, candidate profiles are important information in determining choices, as well as in general elections. Based on these problems, the author conducted a study or analysis using a constructivist paradigm approach using a normative legal approach method which is descriptive analytical in nature. Data sources were obtained from primary and secondary data sources consisting of primary legal materials and secondary legal materials and relevant library documents. From the results of the study carried out, it was found that data from candidates for members of the DPR, DPD, Provincial DPRD and Regency/City DPRD is legally included in the category of data that is exempt or of a private nature so that it requires permission from the data owner to be published as public information and is based on the theory of popular sovereignty. that this data is information needed by the people in making their choices, so it must be opened to the public as a fulfillment of the principle of openness in elections.